The Language of Modern Music - Mitchell, Donald (London Faber & Faber, 1963)
This is a study of the ideas and creative forces that went into shaping the language of 20th-century music. The author's argument is based on a consideration of Schoenberg and Stravinsky, during the course of which he makes forays into the related arts.--This text refers to an out of print or unavailable edition of this title.